Looking beyond? : shifting views of transcendence in philosophy, theology, art, and politics - Stoker, W.; Van der Merwe, W. L. 1957- (Currents of Encounter, 2012)
Religion is undergoing a transformation in current Western society. In addition to organized religions, there is a notable movement towards spirituality that is not associated with any institutions but in which experiences and notions of transcendence are still important. Transcendence can be described as God, the absolute, Mystery, the Other, the other as alterity, depending on one's worldview. In this book, these shifts in the views of transcendence in various areas of culture such as philosophy, theology, art, and politics are explored on the basis of a fourfold heuristic model (proposed by Wessel Stoker). In conversation with this model, various authors, established scholars in their fields, explain the meaning and role, or the critique, of transcendence in the thought of contemporary thinkers, fields of discourse, or cultural domains. Looking Beyond? will stimulate further research on the theme of transcendence in contemporary culture, but can also serve as a textbook for courses in various disciplines, ranging from philosophy to theology, cultural studies, literature, art, and politics.